Development, Swarming, Colony Orphaning And Fly Parasitism In Subterranean Termites, Macrotermes Gilvus (Hagen) And Macrotermes Carbonarius (Hagen) (Blattodae: Termitidae) - Neoh , Kok Boon (2010)
Biological and ecological aspects of Macrotermes gilvus (Hagen) and Macrotermes carbonarius (Hagen) namely: (1) the caste development; (2) flight phenologies and reproductive isolation mechanisms; (3) the impact of orphaning in field colonies; (4) fly larva parasitism in both species were focused in this study. The present research provides insight into termite’s caste developmental pathways, population biology, colony breeding structures and community ecology.